2020
DOI: 10.3390/ijerph17238735
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dyslipidaemia among Type 2 Diabetes Mellitus Patients in the Western Cape, South Africa

Abstract: Dyslipidaemia, an irregular aggregate of lipids in the blood is common in diabetes and cardiovascular disease sufferers. A cross-sectional study on the prevalence of dyslipidaemia was performed among type 2 diabetes mellitus (T2DM) patients in the Western Cape, South Africa. Patients (n = 100) that participated in the study were within the age range of 19–68 years, of whom 89% were observed to have serum lipid abnormalities. Out of the 100 patients, 56%, 64%, 61%, and 65% were recorded to have high total chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
7
2
Order By: Relevance
“…Our result is in line with observations made among patients with DM and hypertension across African countries such as Uganda (88%) 19 , Ethiopia (71.2%) 17 , Kenya (86.1%) 20 and Nigeria (72.4%) 21 . In comparison to observations made across South Africa among patients with DM and/or hypertension, the prevalence reported in the current study was slightly lower than the 89% observed in Cape Town 22 , 90% observed in Durban 23 and 93.5% that was reported in Johannesburg 24 . In addition, countries such as China (31.8%) 18 and Germany (64.5%) 25 reported a lower prevalence of dyslipidaemia in individuals with DM and/or hypertension in comparison to the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…Our result is in line with observations made among patients with DM and hypertension across African countries such as Uganda (88%) 19 , Ethiopia (71.2%) 17 , Kenya (86.1%) 20 and Nigeria (72.4%) 21 . In comparison to observations made across South Africa among patients with DM and/or hypertension, the prevalence reported in the current study was slightly lower than the 89% observed in Cape Town 22 , 90% observed in Durban 23 and 93.5% that was reported in Johannesburg 24 . In addition, countries such as China (31.8%) 18 and Germany (64.5%) 25 reported a lower prevalence of dyslipidaemia in individuals with DM and/or hypertension in comparison to the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar findings were reported by Omodanisi et al(52%) in South Africa. [49] Similarly, in a meta-analysis done among Ethiopians living with T2D, the prevalence of low HDL-C was reported as 44.36%, which is similar to the findings of this present meta-analysis. [50] Insulin resistance enhances the increased production of TRLs which exchange triglyceride Isezuo et al [19] 2003 Cross-sectional 40 25% NW Isezuo and Ezunu [20] 2005 Cross-sectional 254 72.4% NW Idogun et al [21] 2007 Cross-sectional 52 30% SS Okafor et al [22] 2008 Cross-sectional 192 89% SW Unadike et al [23] 2008 Cross-sectional 32 68.7% SS Ogbera et al [24] 2009 Cross-sectional 600 89% SW Kayode et al [25] 2010 Cross-sectional 113 50.4% SW Edo and Adediran [26] 2011 Cross-sectional 52 32.7% SS Jisieike-Onuigbo et al [27] 2011 Cross-sectional 108 90.7% SE Okafor et al [22] 2012 Cross-sectional 233 97.1 SE Oyelade et al [28] 2013 Cross-sectional 219 58.5% SW Edo et al [29] 2014 Retrospective 63 30.2% SS Ogedengbe and Ezeani [30] 2014 Cross-sectional 106 50.8% SE Edo and Edo [31] 2016 Retrospective 130 29.2% SS Enikuomehin et al [32] 2016 Cross-sectional 300 50.4% SW Fasanmade et al [33] 2016 Cross-sectional 218 80.7% SW Young and Onyenekwe [34] 2016 Cross-sectional 51 82.4% SE Omotoye and Fadupin [35] 2017 Cross-sectional 50 70% SW Engwa et al [36] 2018 Cross-sectional 72 40.8% SE Bello-Ovosi et al [37] 2019 Cross-sectional 322 69.3% NW Jaja and Yarhere [38] 2019 Cross-sectional 22 86.4% SS Amadi et al [39] 2020 Retrospective 346 46.8% SS NW: North-west, SS: South-south, SW: South-west, SE: South-east with cholesterol on HDL-C, making the HDL-C more susceptible to increased clearance from the bloodstream.…”
Section: Discussionsupporting
confidence: 90%
“…[48] However, this is markedly different from the findings of Omodanisi et al who reported the prevalence of 64% in their study done in South Africa. [49] Differences in study design and demographics may be partly responsible for these differences. Insulin resistance and hyperglycemia cause increased production of TG-rich lipoproteins (TRLs), reduced clearance of TRLs, and suboptimal metabolism of postprandial triglyceride spike.…”
Section: Discussionmentioning
confidence: 99%
“…This was, however, close to the proportions of nations with similar degrees of development in the available literature. The rate, for example, was reported as 95% in Tanzanian study [ 24 ] and 89% from South Africa [ 25 ]. Another study from Nigeria found the rate to be 69.3% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%